Cultural conceptualisations in Nigerian Pidgin English proverbs - Callies, Marcus (World Englishes, 2024)
This article explores Nigerian Pidgin English proverbs as a source of cultural conceptualisations that reflect traditional wisdom as well as the modern urban setting of West Africa. A total of 173 proverbs sourced from the BBC News Pidgin's Instagram service were analysed for recurrent lexical keywords and themes (e.g. those relating to food, eating and drinking, and animals) that can be interpreted as source domain lexical material that points to the knowledge of nature, common animals, objects and social situations. The findings suggest that Nigerian Pidgin English proverbs contain a rich inventory of variety‐ and culture‐specific lexis that encodes cultural knowledge and practice, for example knowledge of the local flora and fauna, food items, but also objects of material culture such as clothing, as well as references to social culture.